História da ciência luso-brasileira: Coimbra entre Portugal e o Brasil - Carlota Simões (Documentos, 2013)
With the growing interest in history of science, it is worthwhile finding out more about the role of the University of Coimbra in developing science in Portugal and Brazil. This book offers a brief overview of the history of Luso-Brazilian science, focusing on the role of the University in developing science in the two countries from the beginning of the 16th century (Brazil was discovered in 1500) until the middle of 1949 (when the Nobel Prize in Medicine was awarded to Egas Moniz, who is still today the only Nobel prize winner in the area of sciences in the whole Portuguese-speaking world). The work attempts to maintain a balance between historical periods, scientific disciplines and authors from each side of the Atlantic, providing a multi-faceted portrait of science in the Luso-Brazilian world. As such it forms an essential springboard for further studies.